2000
DOI: 10.1007/s002390010118
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of the Neighbor-Joining Method in Reconstructing Deep and Shallow Evolutionary Relationships in Large Phylogenies

Abstract: The neighbor-joining (NJ) method is widely used in reconstructing large phylogenies because of its computational speed and the high accuracy in phylogenetic inference as revealed in computer simulation studies. However, most computer simulation studies have quantified the overall performance of the NJ method in terms of the percentage of branches inferred correctly or the percentage of replications in which the correct tree is recovered. We have examined other aspects of its performance, such as the relative e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
60
0
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 95 publications
(61 citation statements)
references
References 28 publications
0
60
0
1
Order By: Relevance
“…In total, 249 sequences of BenA (for 64 species) and 282 sequences of ITS (for 49 species) were downloaded, aligned by using ClustalW with BioEdit (38), and analyzed in MEGA3 (39). For all analyses, nucleotide-sequence divergences and dendrograms were calculated with the neighborjoining algorithm and the Kimura two-parameter model; the performance of this method is comparable with other techniques when distances are low (40) and large species assemblages are analyzed (41).…”
Section: Methodsmentioning
confidence: 99%
“…In total, 249 sequences of BenA (for 64 species) and 282 sequences of ITS (for 49 species) were downloaded, aligned by using ClustalW with BioEdit (38), and analyzed in MEGA3 (39). For all analyses, nucleotide-sequence divergences and dendrograms were calculated with the neighborjoining algorithm and the Kimura two-parameter model; the performance of this method is comparable with other techniques when distances are low (40) and large species assemblages are analyzed (41).…”
Section: Methodsmentioning
confidence: 99%
“…The NJ methodology is the standard method of phylogenetic inference in DNA barcoding studies (Hebert et al, 2003); its use in DNA barcoding studies is in part due to its strong track record in being able to rapidly analyze large species assemblages (Kumar and Gadagkar, 2000). The chosen molecular substitution model was the computationally simple Kimura-two-parameter (K2P) (Kimura, 1980) which is the standard model of molecular evolution used in DNA barcoding studies (Hebert et al, 2003).…”
Section: Phylogenetic Analyses and Hypotheses Testingmentioning
confidence: 99%
“…We used a short fragment (221 bp) of dsrA to reconstruct phylogenetic trees. Sequence length has a profound effect on reliable reconstruction of phylogenetic trees (Kumar & Gadagkar 2000). Pérez-Jiménez et al (2001) tested whether the length of dsrAB used for the analysis had a significant effect on the tree topology by reconstructing phylogenetic trees for alignments of different length dsrAB sequences and found that the general topology of all trees was consistent with the previous dsrAB tree based on fulllength dsrAB fragments (Minz et al 1999, Wagner et al 1998.…”
mentioning
confidence: 94%